Effect of Saturated Fatty Acids on the Antiwear and Rheological Properties of Olive Oil - M.S. Charoo; Fozia Akhter; Muhammad Hanief; Wani Khalid Shafi; Mehak Nissar (Tribology in Industry, 2023)
The study determines the effect of saturated fatty acids (coconut oil) on the rheological and tribological properties of olive oil. The olive oil is blended with different proportions of coconut oil (10%, 20%, 30%, 40%, and 50%) and the different properties (flow behaviour and antiwear) are studied on Anton Paars rheometer and Four-ball tester respectively. The study reveals that the blends depict Newtonian behaviour with a decrease in the dynamic viscosity of the olive oil. Also, WSD decreases at a higher proportion of coconut oil in the blends with an improvement of 10.74% at a 50:50 ratio. The blending of two oils for the enhancement of the lubrication properties of biolubricants can prove beneficial in making them a suitable replacement for mineral oils.